Lithium-ion Battery Electro-thermal Modelling and Parameters Estimation - Elsaadany, Mazen Essam (2022)
A Master of Science thesis in Electrical Engineering by Mazen Essam Elsaadany entitled, “Lithium-ion Battery Electro-thermal Modelling and Parameters Estimation”, submitted in June 2022. Thesis advisor is Dr. Shayok Mukhopadhyay and thesis co-advisor is Dr. Habib-ur Rehman. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).